Alternative formulations for gilthead seabream diets: Towards a more sustainable production. (28th October 2019) - Aragão, Cláudia; Cabano, Miguel; Colen, Rita; Fuentes, Juan; Dias, Jorge
Abstract: To support the expected increase in aquaculture production during the next years, a wider range of alternative ingredients to fishmeal is needed, towards contributing to an increase in production sustainability. This study aimed to test diets formulated with non‐conventional feed ingredients on gilthead seabream ( Sparus aurata ) growth performance, feed utilization, apparent digestibility of nutrients and nutrient outputs to the environment. Four isonitrogenous and isoenergetic diets were formulated: a control diet (CTRL) similar to a commercial feed and three experimental diets containing, as main protein sources, plant by‐products, glutens and concentrates (PLANT); processed animal proteins (PAP); or micro/macroalgae, insect meals and yeast (EMERG). Diets were tested in triplicate during 80 days. The EMERG treatment resulted in lower fish growth performance, higher FCR and lower nutrient and energy retentions than the other treatments. The lowest protein digestibility was found for the EMERG diet, which caused increased nitrogen losses. The PLANT and PAP treatments resulted in better fish growth performance, higher nutrient and energy retentions, and lower FCR than the CTRL treatment. The significant improvement in FCR found for fish fed PLANT and PAP diets and the high protein digestibility of these diets contribute towards minimizing the environmental impacts of seabream production.